Determination of leachate toxicity through acute toxicity using Daphnia pulex and anaerobic toxicity assays (2017)
The municipal solid waste (MSW) of large cities, in particular in developing countries, is mainly disposed of in landfills (LFs), whose inadequate management generates the emission of greenhouse gases and the production of leachates with high concentrations of organic and inorganic matter and occasionally heavy metals. In this study, the toxicity of the leachates from an intermediate-age municipal landfill was evaluated by ecotoxicity and anaerobic digestion tests. The acute toxicity assays with Daphnia pulex presented a toxic unit (TU) value of 49.5%, which indicates that these leachates should not be directly discharged into water sources or percolate into the soil because they would affect the ecosystems served by these waters. According to statistical analyses, the leachate toxicity is mainly associated with the inorganic fraction, with chlorides, calcium hardness and calcium having the greatest influence on the toxicity. The anaerobic toxicity assays showed that in the exposure stage, the methanogenic activity exceeded that of the control, which suggests that the anaerobic bacteria easily adapted to the leachate. Therefore, this treatment could be an alternative to mitigate the toxicity of the studied leachates. The inhibition presented in the recovery stage, represented by a reduction of the methanogenic activity, could arise because the amount of supplied substrate was not enough to fulfill the carbon and nutrient requirements of the bacterial population present.